Analysis of Factors Influencing Consumer Purchasing Decisions in the Digital Era - Akbar, Faizin Rahmadi; Mukhid, Mukhid (Nomico, 2026)
Consumer purchase behavior has undergone a fundamental transformation in the digital age due to the intricate interactions between individual traits, product qualities, digital experiences, online marketing tactics, and consumer trust. In order to combine these elements and create a conceptual framework of digital consumer behavior, this study uses a systematic literature review method, reviewing research produced between 2020 and 2026. The results show that customers' capacity to traverse digital platforms is influenced by individual variables such age, education level, digital literacy, and personal preferences. In order to lower perceived risk and boost confidence, product factors such as quality, pricing, brand reputation, and perceived value are crucial. Engagement, loyalty, and purchase decisions are all improved by positive digital experiences, tailored marketing tactics, and high levels of consumer trust. In addition to providing useful insights for business practitioners and theoretical contributions for future research, this study highlights the significance of an integrated strategy that takes into account all influencing aspects to understand digital consumer behavior.